2022
DOI: 10.1002/jemt.24076
|View full text |Cite
|
Sign up to set email alerts
|

Lingual papillary system of the Egyptian mouse‐tailed bat (Rhinopoma hardwickii): New insights to its feeding strategies using scanning electron microscope, and immunohistochemical analysis of keratin

Abstract: The current investigation described the ultrastructural and histological features of the lingual papillary system in 14 adult Rhinopoma hardwickii using scanning electron and light microscopy, and immunohistochemical staining of keratin. Three types of lingual papillae were recognized; one filiform mechanical and two gustatory (fungiform and circumvallate) of three directions: posterior, posteromedian, and median.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The topographical distribution of the different lingual papillae types has specific-region variations (Kandyel et al, 2021). Moreover, the papillary variations are extended to their appearance, size, directions, microstructure and terminology (Abumandour et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topographical distribution of the different lingual papillae types has specific-region variations (Kandyel et al, 2021). Moreover, the papillary variations are extended to their appearance, size, directions, microstructure and terminology (Abumandour et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The topographical distribution of the different lingual papillae types has specific‐region variations (Kandyel et al, 2021). Moreover, the papillary variations are extended to their appearance, size, directions, microstructure and terminology (Abumandour et al, 2022). The morphological adaptations of the lingual papillae are primarily related to nutritional habits and mechanisms, dietary nature and environmental conditions (Iwasaki, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The two conical papillary subtypes are recorded on the tongues of herbivorous animals (Mahdy et al, 2021), although one type of the conical papillary subtype is observed in some herbivorous animals (Kurtul & Atalgin, 2008). The mechanical papillae have a great role in food particle capture and manipulation and are characterized by their morphological variations among mammalian species (Abumandour et al, 2022). There are species variations in the morphological appearance of the mechanical papillae that are correlated with the available food particles, the feeding behaviour and the geographical distribution (El-Mansi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the tongue is the most distinctive structure of the oral cavity contents, describing the morphological adaptations of each animal species in relation to accessible food particles (Abumandour et al, 2022; Iwasaki, 2002). Contents and relates to the morphological adaptations of each animal species to accessible food materials (El‐Mansi, El‐Bealy, Al‐Kahtani, et al, 2021; El‐Mansi, El‐Bealy, Rady, et al, 2021; Iwasaki, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation